2010
DOI: 10.1101/gad.1946410
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial, site-specific requirement for heterochromatic silencing factors in the elimination of nucleosome-free regions

Abstract: High-resolution nucleosome occupancy maps of heterochromatic regions of wild-type and silencing-defective mutants of the fission yeast Schizosaccharomyces pombe revealed that heterochromatin induces the elimination of nucleosome-free regions (NFRs). NFRs associated with transcription initiation sites as well as those not associated with promoters are affected. We dissected the roles of the histone H3K9 methyltransferase Clr4 and the HP1 proteins Swi6 and Chp2, as well as the two catalytic activities of the SHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 60 publications
6
92
0
Order By: Relevance
“…This is consistent with the H3 ChIP-seq and nucleosome positioning data that show a nucleosome-free region between SPAC212.10 and SPAC212.09c in caf1Δdcr1Δ (Fig. 3B) and clr4Δ cells (Garcia et al 2010). Northern blot analysis confirms that tlh RNA is longer in caf1Δdcr1Δ and caf1Δago1Δ cells than in ago1Δ or caf1Δ cells (Fig.…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgsupporting
confidence: 77%
“…This is consistent with the H3 ChIP-seq and nucleosome positioning data that show a nucleosome-free region between SPAC212.10 and SPAC212.09c in caf1Δdcr1Δ (Fig. 3B) and clr4Δ cells (Garcia et al 2010). Northern blot analysis confirms that tlh RNA is longer in caf1Δdcr1Δ and caf1Δago1Δ cells than in ago1Δ or caf1Δ cells (Fig.…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgsupporting
confidence: 77%
“…Previous studies have implicated a role for Mit1 in positioning nucleosomes (19,20). In this study, we demonstrated that Mit1 is indeed a nucleosome remodeling factor capable of mobilizing histone octamers in vitro, with characteristics similar to those of Mi-2 remodelers.…”
mentioning
confidence: 50%
“…One mechanism by which heterochromatin can restrict RNA polymerase II accessibility is through altering nucleosomal occupancy to prevent access of transcription factors to their target sequences. Heterochromatin prevents the appearance of nucleosome-free regions (NFRs) at various locations in silenced regions of the genome, and nucleosome occupancy at some of these sites has been shown to depend on Mit1/SHREC (7,9,20,39). Interestingly, the sites that most depend on Mit1 do not map to sites of transcription initiation or to regions particularly enriched for RNA Pol II.…”
Section: ⌬Phd and Mit1mentioning
confidence: 99%
“…The recent finding that different NDRs depend on the binding of different proteins and epigenetic modifications in S. pombe (Garcia et al, 2010) and in S. cerevisiae (Bai et al, 2011) suggests that only some combinations of them would make a NDR competent for recruiting the recombination machinery.…”
Section: Specification Of Meiotic Dsb Sites In S Pombementioning
confidence: 99%